Cambrian, Ordovician and Silurian non-stromatoporoid Porifera - Muir, Lucy A. (2013)
The Cambrian, Ordovician and Silurian distributions of non-stromatoporoid sponges are reviewed. The earliest Cambrian faunas contain mostly hexactinellids, with protomonaxonids dominating middle Cambrian assemblages. There are no obvious palaeobiogeographical patterns, with many genera being found widely. Vauxiids, lithistids and heteractinids are apparently confined to low latitudes, but this may be due to a poor fossil record. Most known Ordovician faunas are from low latitudes, although some high-latitude faunas are known, which contain reticulosan hexactinellids and protomonaxonids. There is some division of faunas within Laurentia, into eastern and western provinces, with the western assemblage extending across low northern latitudes during the Late Ordovician. During the Silurian Period, sponge diversity was very low during the Llandovery Epoch, probably partly owing to lack of habitat for taxa restricted to carbonate facies, and also because of sampling bias. There was a dramatic increase in diversity through the Silurian Period, mostly owing to an apparent diversification in the demosponges; however, there are many ghost lineages, indicating that their fossil record is poorly known. Non-lithistid sponges are very poorly known, with few recorded outside Euramerica. The currently available data for Early Palaeozoic sponges are too incomplete to allow any reliable palaeobiogeographical inferences.